Adopsi Inovasi Teknologi Sambung Samping Dalam Peremajaan Kakao Oleh Petani Subakabian Padma Sari, Kecamatan Melaya, Kabupaten Jembrana - WARMAN, I PUTU ADITYA; PUTRA, I GEDE SETIAWAN ADI; ASTITI, NI WAYAN SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022, 2022)
Adoption of Side Cleft Grafting Technology Innovations in Cocoa Rejuvenation by Farmers Subakabian Padma Sari, Kec. Melaya, Kab. Jembrana Subakabian Padma Sari is one of the farmer groups that has implemented unproductive cocoa rejuvenation using side grafting technology innovations side cleft grafting in cocoa rejuvenation. The research was conducted from January to March 2021 in Subakabian Padma Sari, Nusasari Village, Melaya District, Jembrana Regency. Sampling using simple random sampling technique  with the calculation of the formula Slovin , the research sample is 50 farmers. Methods of data collection through in-depth interviews and structured interviews (questionnaires), then analyzed using a qualitative descriptive method. The results showed that the characteristics of farmers in Subakabian Padma Sari have an average age belonging to productive age, education level at high school level, experience in cocoa farming, small number of family dependents, narrow land area, small population of cocoa trees, and most of them cultivate. follow-up clone varieties. The stages of the adoption process of side-grafting technology innovations have a graph of decreasing stages from the conscious stage to the adoption stage. The pace of innovation adoption is slow, which is influenced by six factors, namely: the nature of innovation is moderate, the type of decision making is good, the nature of the target is slow, the communication channel is good, the social system is good, and the role of reforming agents is moderate. Cocoa farmers in Subakabian Padma Sari should spend more time on cocoa cultivation, because side-grafting technology innovations can increase production yields, thereby increasing farmers' income. Extension workers should be more aggressive in introducing side-grafting technology innovations, by providing intensive assistance to farmers, paying attention to the innovation decision process starting from the conscious stage to adopting the innovation given. The innovator should disseminate side-grafting technological innovations by showing evidence of success that other farmers can observe directly.